Social Causation, Social Selection, or Common Determinants? Examining Competing Explanations for the Link Between Young Adult Unemployment and Nicotine Dependence. Issue 11 (13th August 2019) - Lee, Jungeun Olivia; Horwood, L John; Lee, Woo Jung; Hackman, Daniel A; McLeod, Geraldine Fh; Boden, Joseph M
Abstract: Introduction: Unemployment has been related to smoking, yet the causal nature of the association is subject to continued debate. Social causation argues that unemployment triggers changes in smoking, whereas the social selection hypothesis proposes that pre-existing smoking behavior lowers the probability of maintaining employment. The present study tested these competing explanations while accounting for another alternative explanation—common liability. Methods: Data were from the Christchurch Health and Development Study, a longitudinal cohort followed from birth to age 35. Odds were generated for having nicotine dependence in models for social causation and being unemployed in models for social selection. These models were extended to include possible common liability factors during childhood (eg, novelty seeking) and young adulthood (eg, major depression). Results: In the model testing social causation, coefficients representing the impacts of unemployment on nicotine dependence remained statistically significant and robust (odds ratio [OR] = 1.55; 95% confidence interval [CI] = 1.20, 2.00), even after accounting for common determinant measures. In contrast, a reverse social selection model revealed that coefficients representing the impacts of nicotine dependence on unemployment substantially attenuated and became statistically nonsignificant as childhood factors were added (OR = 1.14; 95% CI = 0.90, 1.45). Conclusions: Unemployment may serve as inroads to nicotine addiction among young adults, not the other way, even in the context of nicotine dependence, a more impaired form of smoking that may arguably hold higher potential to generate social selection processes. This social causation process cannot be completely attributable to common determinant factors. Implications: It is critical to clarify whether unemployment triggers changes in smoking behaviors (ie, social causation) or vice versa (ie, social selection)—the answers to the question will lead to public health strategies with very different intervention targets to break the linkage. The current study findings favor social causation over social selection, regardless of gender, and support a needed shift in service profiles for unemployed young adults—from a narrow focus on job skills training to a more holistic approach that incorporates knowledge from addiction science in which unemployed young adults can find needed services to cope with job loss.